The Lhx4 homeobox transcript in the rat pineal gland: Adrenergic regulation and impact on transcripts encoding melatonin‐synthesizing enzymes. Issue 1 (11th November 2019) - Hertz, Henrik; Carstensen, Mikkel B.; Bering, Tenna; Rohde, Kristian; Møller, Morten; Granau, Agnete M.; Coon, Steven L.; Klein, David C.; Rath, Martin F.
Abstract: Homeobox genes generally encode transcription factors involved in regulating developmental processes. In the pineal gland, a brain structure devoted to nocturnal melatonin synthesis, a number of homeobox genes are also expressed postnatally; among these is the LIM homeobox 4 gene ( Lhx4 ). We here report that Lhx4 is specifically expressed in the postnatal pineal gland of rats and humans. Circadian analyses revealed a fourfold rhythm in Lhx4 expression in the rat pineal gland, with rhythmic expression detectable from postnatal day 10. Pineal Lhx4 expression was confirmed to be positively driven by adrenergic signaling, as evidenced by in vivo modulation of Lhx4 expression by pharmacological (isoprenaline injection) and surgical (superior cervical ganglionectomy) interventions. In cultured pinealocytes, Lhx4 expression was upregulated by cyclic AMP, a second messenger of norepinephrine. By use of RNAscope technology, Lhx4 transcripts were found to be exclusively localized in melatonin‐synthesizing pinealocytes. This prompted us to investigate the possible role of Lhx4 in regulation of melatonin‐producing enzymes. By use of siRNA technology, we knocked down Lhx4 by 95% in cultured pinealocytes; this caused a reduction in transcripts encoding the melatonin‐producing enzyme arylalkylamine N‐acetyl transferase ( Aanat ). Screening the transcriptome of siRNA‐treated pinealocytes by RNAseq revealed a significant impact of Lhx4 on the phototransduction pathway and on transcripts involved in development of the nervous system and photoreceptors. These data suggest that rhythmic expression of Lhx4 in the pineal gland is controlled via an adrenergic‐cyclic AMP mechanism and that Lhx4 acts to promote nocturnal melatonin synthesis.